The Effect of Financial Literacy, Herding Behavior and Risk Tolerance on Investment Decisions - Dewi Tamara; Andhika Yudo Arianto; Ernita Marzuki; Zulhamdani Zulhamdani (Budapest International Research and Critics University, 2022)
Investment development in Indonesia grew significantly, marked by an increase in the Composite Stock Price Index (JCI) which reached 23.54% in the last 5 (five) years. This is in line with increasing financial inclusion, public knowledge and awareness of financial planning and management. Financial investment in the Capital Market, especially stocks, is one of the most favorable by investors, as indicated by the growth in the number of investors on average per year reaching 60.65%. However, the JCI's performance for the last 5 (five) years has not been stable, where prices are still fluctuating. Therefore, investors are required to be more careful in making investment decisions that will affect future returns. In this regard, this study examines the effect of financial literacy, herding behavior and risk tolerance on investment decisions, with self-monitoring as a moderating effect. The results of the study prove that financial literacy, herding behavior and risk tolerance have a significant effect on investment decisions. Meanwhile, self-monitoring is not proven to moderate the relationship between financial literacy, herding behavior, and risk tolerance for investment decisions.